Prognostic impact of simultaneous venous resections during surgery for resectable pancreatic cancer. Issue 10 (October 2020) - Anger, Friedrich; Döring, Anna; Schützler, Julia; Germer, Christoph-Thomas; Kunzmann, Volker; Schlegel, Nicolas; Lock, Johan F.; Wiegering, Armin; Löb, Stefan; Klein, Ingo
Abstract: Background: The aim of this study was to evaluate the prognostic impact of simultaneous venous resection during pancreaticoduodenectomy (PD) for pancreatic adenocarcinoma (PDAC) that was preoperatively staged resectable according to NCCN guidelines. Methods: A retrospective analysis of 153 patients who underwent PD for PDAC was performed. Patients were divided into standard PD and PD with simultaneous vein resection (PDVR). Groups were compared to each other in terms of postoperative morbidity and mortality, disease free (DFS) and overall survival (OS). Results: 114 patients received PD while 39 patients received PDVR. No differences in terms of postoperative morbidity and mortality between both groups were detected. Patients in the VR group presented with a significantly shorter OS in the median (13 vs. 21 months, P  = 0.011). In subgroup analysis, resection status did not influence OS in the PDVR group (R0 13 vs. R1 12 months, P  = 0.471) but in the PD group (R0 23 vs. R1 14 months, P  = 0.043). PDVR was a risk factor of OS in univariate but not multivariable analysis. Conclusion: PDVR for PDAC preoperatively staged resectable resulted in significantly shorter OS regardless of resection status. Patients who require PDVR should be considered for adjuvant chemotherapy in addition to other oncological indications.